2020
DOI: 10.1186/s13018-020-01999-7
|View full text |Cite
|
Sign up to set email alerts
|

The worldwide prevalence of the Dupuytren disease: a comprehensive systematic review and meta-analysis

Abstract: Background The Dupuytren disease is a benign fibroproliferative disorder that leads to the formation of the collagen knots and fibres in the palmar fascia. The previous studies reveal different levels of Dupuytren’s prevalence worldwide; hence, this study uses meta-analysis to approximate the prevalence of Dupuytren globally. Methods In this study, systematic review and meta-analysis have been conducted on the previous studies focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 67 publications
0
22
0
5
Order By: Relevance
“…The disease may affect descendants of northern European ancestry more than other groups; however, results of a 2020 study that included a genetic risk score showed no genetic evidence of a Viking origin for the disease 3 . Results of a literature review of 85 studies on the condition show a current worldwide prevalence rate of 8.2% (95% confidence interval [CI] = 5.7 to 11.7) with the highest prevalence in Africa at 17.2% (95% CI = 13 to 22.3) 4 . In 1831, Baron Guillaume Dupuytren was the first person to formally present a lecture to the medical community on permanent contractions of the flexed fingers and publish his findings; 5 the disease now bears his name 1 .…”
Section: Dupuytren’s Disease Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease may affect descendants of northern European ancestry more than other groups; however, results of a 2020 study that included a genetic risk score showed no genetic evidence of a Viking origin for the disease 3 . Results of a literature review of 85 studies on the condition show a current worldwide prevalence rate of 8.2% (95% confidence interval [CI] = 5.7 to 11.7) with the highest prevalence in Africa at 17.2% (95% CI = 13 to 22.3) 4 . In 1831, Baron Guillaume Dupuytren was the first person to formally present a lecture to the medical community on permanent contractions of the flexed fingers and publish his findings; 5 the disease now bears his name 1 .…”
Section: Dupuytren’s Disease Overviewmentioning
confidence: 99%
“…3 Results of a literature review of 85 studies on the condition show a current worldwide prevalence rate of 8.2% (95% confidence interval [CI] = 5.7 to 11.7) with the highest prevalence in Africa at 17.2% (95% CI = 13 to 22.3). 4 In 1831, Baron Guillaume Dupuytren was the first person to formally present a lecture to the medical community on permanent contractions of the flexed fingers and publish his findings; 5 the disease now bears his name. 1 Since that time, many physicians and surgeons have attempted to treat Dupuytren's disease, but none have been fully successful at eradicating it.…”
Section: Dupuytren's Disease Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of Dupuytren's contracture, a benign fibroproliferative condition with formation of collagen knots and fibres over the palmar fascia is higher in AUD patients particularly those with concomitant diabetes. 133 Patients with ALD most often suffer from sarcopenia (skeletal muscle loss) which can be attributed to hepatocellular dysfunction as well as direct toxic effect of alcohol and its metabolites on muscle tissue leading to reduced synthesis of protein and anabolic resistance and an impaired response to nutritional interventions. 134,135 The prevalence of sarcopenia is higher in alcoholic hepatitis than that in alcoholic cirrhosis which may be attributed to the presence of considerable amount of acute inflammatory response in alcoholic hepatitis.…”
Section: Musculoskeletal Changesmentioning
confidence: 99%
“…За характером супутньої патології як прогностично несприятливим щодо шансів прогресування хвороби й пролонгованого терміну анатомо-функціонального відновлення кисті після оперативної корекції, за даними Nader Salari, Mohammadbagher Heydari et al (2020), є цукровий діабет І типу, найбільша частка пацієнтів становить 34,1% (95% ДІ 25-44,6%) [27].…”
Section: результати та висновки аналіз літературних джерел показав переваги диференційованого підходу до хірургічного лікування хвороби дunclassified